PERAN HAMBATAN STRUKTURAL TERHADAP TINGKAT KEBERDAYAAN PEREMPUAN BALI DALAM JABATAN ESELON DI PROVINSI BALI - Marhaeni, Anak Agung Istri Ngurah (PIRAMIDA, 2012)
Females were empowered as workforce and significantly gave contribution for people’slive and economic advance of family and nation. Increasing of Female Labourforce ParticipationRate (TPAK) occurred both in national level as well as in Bali Province.. The development offemale empowerment in economic subject was not always followed by development of theirwelfare and power to achieve through salary they earned. This was related to job position or theirposition in their jobs.The high percentage of females who were working in the informal sectors became areflection of low female empowerment in economic subjects. Similarly, the average wage earnedby female workers was lower than male worker average wage also became reflection of lowfemale economic empowerment. Female economic empowerment that was lower than males wasalso reflected by female percentage was successful holding echelon position in Bali Provincewas only 22.3 percent from the available positions in 2008, with a relatively high variationaccording to a regency or a town.The objective of this research was to learn based on models developed on influence ordynamics factors of direct or indirect structural obstacle factors through organisational culturetowards Balinese females empowerment in echelon positions. The result from data processingthat structural obstacle was negatively affected to female empowerment grade. This resultresearch was suitable with Davidson’s (1996) statement that obstacle in an organization faced byfemales in their efforts to develop females in workplace was obstacles related to attitude andstructural obstacles. Structural obstacle could include procedure, personnel policy, and practisesin the organization. Organizational policy and practice could create obstacles to female careerdevelopment (Bielby, 2000). Discrimination experienced by females in personnel policy couldinclude recruitment process, promotional evaluation system, and training’s opportunity.
Keywords: Structural obstacle, empowerment, echelon positions